A poética da emulação no de Rerum natura - Aguiar, Saulo Santana de (2017)
The poem De rerum natura, by Lucretius, may be considered one of the greatest masterpieces of all Latin literature, having been composed in the first half of the first century BC, with a clear didactic intention to propagate the epicureanism in the middle of the Roman society of that time, weakened by wars and political conflicts of enormous relevance. In view of the fragmentation of the social structure of the urbs, based on a republican system in deep débâcle, the poet Titus Lucretius Carus, fervent adept of the philosophy of Epicurus, saw in this doctrine an important way of moral salvation for corruption of the customs in his generation. Epicurus praised an attitude of total abstention from political life as well as from search for wealthies, in order to reach true happiness, through the study of nature and its laws, and freedom from death and gods’ fear. Despite the pragmatic objectives attributable to the Lucretian’s intent, there is no doubt as to the literary value of his work, due to its notorious mimesis of cosmic order. At the same time, it is also possible to perceive in the poetic construction of the De rerum natura innumerable allusions and references to other texts, either of the didactic aspect as the great classical epic’s one, going back to a fruitful emulative dialogue between Lucretius and all literary tradition. Thus, the purpose of this work is to analyze Book one of poem, based on the understanding of a poetic that reflects its mimetic relations with the other works that make up the epic-didactic poetry. For this purpose, we shall use Palimpsestes: la littérature au second degré, by Gérard Genette, as a theoretical basis for our research, which will provide us with the necessary background to the study of literature under the key of comparativism; As well as, the theoretical contribution of earlier authors who endeavored to understand the phenomenon of mimesis in art, such as Plato, Aristotle, Quintilian, and others, will serve as resource.